Психофизиологическая коррекция тревожно депрессивных расстройств у больных дорсопатией = Psychophysiological correction anxious depressive disorders in patients dorsopathy - Chuhraev, N V; Vladimirov, A A; Levkovskaya, V I; Zukow, W (Journal of Education, Health and Sport, 2015)
Chuhraev N V, Vladimirov A A, Levkovskaya V I, Zukow W. Психофизиологическая коррекция тревожно депрессивных расстройств у больных дорсопатией = Psychophysiological correction anxious depressive disorders in patients dorsopathy. Journal of Education, Health and Sport. 2015;5(6):273-280. ISSN 2391-8306. DOI 10.5281/zenodo.18566 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A273-280 https://pbn.nauka.gov.pl/works/566018 http://dx.doi.org/10.5281/zenodo.18566 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 14.06.2015. УДК 612.821+615.831.8 Психофизиологическая коррекция тревожно депрессивных расстройств у больных дорсопатией Psychophysiological correction anxious depressive disorders in patients dorsopathy Н. В. Чухраев1, А. А. Владимиров1, В. И.Левковская2, W. Zukow3 N V Chuhraev1, A A Vladimirov1, V I Levkovskaya2, W Zukow3 1 ООО «НМЦ Мединтех», Киев, Украина 2 Государственное учреждение «Дорожная клиническая больница №2 ст.Киев ГОТО "ЮЗД", Киев, Украина 3 Kazimierz Wielki University, Bydgoszcz, Poland 1 « NMC Medintech " , Kiev, Ukraine 2 State Institution " Road Clinical Hospital №2 st.Kiev GOTO " YUZD " Kiev, Ukraine 3 Kazimierz Wielki University, Bydgoszcz, Poland Аннотация В статье приведены результаты лечения больных дорсопатией на основе многоуровневого подхода в сочетании с психофизиологической коррекцией тревожно депрессивных расстройств. Ключевые слова: магнитолазерная терапия, психофизиологическая коррекция, тревожно депрессивные расстройства, дорсопатия. Abstract In the article the results of treatment of patients with dorsopathies on the basis of the multilevel approach in combination with psychophysiological correction anxiety depressive disorders. Keywords: magneto-laser-therapy, psycho-physiological correction, anxious depressive disorders, dorsopathies. Анотація У статті наведено результати лікування хворих дорсопатией на основі багаторівневого підходу в поєднанні з психофізіологічної корекцією тривожно-депресивних розладів. Ключові слова: магнітолазерна терапія, психофізіологічна корекція, тривожно депресивні розлади, дорсопатія.